Antiobesity activity of Elateriospermum tapos shell extract in obesity-induced sprague Dawley rats - Perumal, Kokila Vani; Ja’afar, Nor Liyana; Mat Taib, Che Norma; Shafie, Nurul Husna; Bahari, Hasnah (Multidisciplinary Digital Publishing Institute, 2021)
Obesity is one of the risk factors associated with cardiovascular diseases, hypertension, abnormal liver function, diabetes, and cancers. Orlistat is currently available to treat obesity, but it is associated with adverse side effects. Natural resources are widely used for obesity treatment. Hence, this study aimed to investigate the anti-obesity activity of Elateriospermum tapos (E. tapos) shell extract in obesity induced Sprague Dawley rats. The rats’ obesity was induced by a high-fat (HF) diet made up of 50% standard rat pellet, 20% milk powder, 6% corn starch, and 24% ghee and a cafeteria (CAF) diet such as chicken rolls, salty biscuits, cakes, and cheese snacks. A hot aqueous method for the extraction of E. tapos shells was applied by using 500 mL of distilled water for about 24 h. Various dosages of E. tapos shell extract (10 mg/kg, 100 mg/kg, and 200 mg/kg) were used. At the end of the study, body weight, caloric intake, organ weight, lipid profile, lipoprotein lipase (LPL) activity, and histopathology analysis were carried out. E. tapos shell extract treated groups showed a reduction in body weight, positive lipid-lowering effect, decrements in triglyceride accumulation and LPL activity, and positive improvement in histopathology analysis. A dose of 200 mg/kg showed the most effective result compared to 10 mg/kg and 100 mg/kg doses.